1996
DOI: 10.1017/s1049023x00042345
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Demand for First-Aid Care at a Major Public Event

Abstract: Introduction:First aid is the initial care of the ill or injured. It aims to preserve and protect life, prevent further injury or deterioration of illness, and help promote recovery. At major public events, there is a large gathering of people, physical spectacles, and equipment within a concentrated area, where organized first-aid care is provided.Objective:To analyze the demand for primary medical care at a public event by identifying the patients and initial symptoms that may predict that demand, and to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 14 publications
2
27
0
3
Order By: Relevance
“…Although there is a growing body of literature examining medical consultations at mass gatherings (Sanders et al, 1986;Flabouris and Bridgewater, 1996;Shelton et al, 1997;Crawford et al, 2001;Martin-Gill et al, 2007) there is little literature in the area of English league football. The authors could find no published studies carried out on crowd medical services in English league football, (Pubmed, CINHAL, HILO/Ovid using keywords ''football '', ''soccer'', ''crowd'', ''safety'' and ''mass gathering'').…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a growing body of literature examining medical consultations at mass gatherings (Sanders et al, 1986;Flabouris and Bridgewater, 1996;Shelton et al, 1997;Crawford et al, 2001;Martin-Gill et al, 2007) there is little literature in the area of English league football. The authors could find no published studies carried out on crowd medical services in English league football, (Pubmed, CINHAL, HILO/Ovid using keywords ''football '', ''soccer'', ''crowd'', ''safety'' and ''mass gathering'').…”
Section: Introductionmentioning
confidence: 99%
“…Routine staffing consists of one Advanced Life Support (ALS) trained physician, two ALS trained nurses and fifteen members of a voluntary service agency, St John Ambulance (SJA) who hold a minimum of a first-aid certificate. By definition first-aid is the initial care of the ill or injured (Flabouris and Bridgewater, 1996) and individuals holding this level of skill make up the majority of healthcare providers at The Den. In addition to the presence of the London Ambulance Service crew and officer, an ambulance staffed by trained St John members is also in attendance providing a multi-disciplinary team approach.…”
Section: Introductionmentioning
confidence: 99%
“…The Royal Adelaide Show was chosen as the principal mass gathering for the study based on previous work. 4,7,8 The Royal Adelaide Show, an agricultural and horticultural show, has an average attendance of 616,000 patrons over the nine days. While St. John and Workplace Services are on-site, there are no rostered Medical Officers.…”
mentioning
confidence: 99%
“…Data available from this review included crowd size, number of patient presentations, weather, and the number of patients transferred to hospitals by ambulances (1996)(1997)(1998)(1999)(2000)(2001). The inferences derived from seven years of data indicated that the significant factors predicting medical workload for this 5 and an injury surveillance study was undertaken to explore injuries that occur at a mass-gathering event. 7…”
mentioning
confidence: 99%